Isolement et identification de quelques champignons d’un sol pollué par les hydrocarbures - KOIBICH, Nabila (My University, 2016)
Hydrocarbons are a major pollutant of soil. Biodegradation of petroleum products through the soil microorganisms has emerged as a method of interest for economic and ecological point of view. The aim of our study was to isolate and identify fungi species present in soil polluted by hydrocarbons: crude oil, diesel and used oil motor. The soil sample was polluted with these hydrocarbon derivatives for 6 months. Isolation of fungi isolates were carried out using the dilution method, whereas the identification of fungi was based on their morphology depending on macroscopic and microscopic appearance. A number of fungi isolates were isolated from three types of polluted soils on PDA medium. The results showed the presence of two different fungi genera namely: Aspergillus and Penicillium, with the dominance of isolates belonging to the genus Aspergillus. Four isolates were selected for the test of their ability to degrade crude oil. These were grown on three different salt medium: without any carbon source, with sucrose as a carbon source and salt medium supplemented with 1% crude oil as a carbon source. Unfortunately the chosen isolates were unable to degrade crude oil.
Keywords: Oil; Biodegradation; Fungi; Aspergillus; Penicillium.; النفط; التحليل البيولوجي; الفطريات